Addition of organolithium nucleophiles to the diiron allenyl complex [Fe2(CO)6(μ-PPh2){μ-η1: η2 α,β-(H)Cα=Cβ =CγH2}]:Synthesis and characterization of organodiiron-coordinated β,γ-unsaturated ketones - Doherty, S; Elsegood, M; Clegg, W; Rees, N; Scanlan, T; Waugh, M (1997)
The binuclear allenyl complex [Fe2(CO)6(μ-PPh2){μ-η 1:η2α,β-(H)C α=Cβ=CγH2}] (1) has been prepared, and its reactivity with organolithium nucleophiles is described. Prop-2-yne bromide reacts with [Fe2(CO)7(μ-PPh2)]-Na +, via an SN2 mechanism, to give [Fe2(CO)6(μ-PPh2){μ-η1: η2α,β-(H)Cα=C β=CγH2}], the first example of a phosphido-bridged allenyl complex. The molecular structure of [Fe2(CO)6(μ-PPh2){μ-η 1:η2-(H)Cα=Cβ=C γH2}]: (1) was determined by single-crystal X-ray diffraction and shows that the allenyl ligand is coordinated through Cα-Cβ. Variable-temperature 1H and 13C NMR studies reveal a high-energy exchange process that equilibrates the diastereotopic allenyl protons, presumably via a zwitterionic intermediate, as well as two independent trigonal rotations that act to exchange the carbonyl ligands on each unique Fe(CO)3 group. Complex 1 reacts with organolithium reagents (RLi; R = Me, nBu, Ph, C4H3S), via allenyl-carbonyl-nucleophile coupling, to afford the binuclear β,γ-unsaturated ketones [Fe2(CO)5{P(OMe)3}(μ-PPh 2)(μ-η1:η2-{RC(O)CH 2}C=CH2)] (R = Me, 3a; nBu, 3b; Ph, 3c; C4H3S, 3d), and a single-crystal X-ray structure determination of 3a was undertaken to confirm the connectivity of the hydrocarbyl ligand. The most likely mechanism for the formation of 3a-d involves nucleophilic attack of R- at CO to give an acylate intermediate followed by migration of RCO to Cα of the allenyl and protonation of the resulting enolate to give the unstable alkenyl complexes [Fe2(CO)5(μ-PPh2)(μ-η 1(C):η1-(C):η2(C)-{RC(O)CH 2}C=CH2)] (R = Me, 2a; Bu, 2b; Ph, 2c; C4H3S, 2d). Finally, substitution of the metal-coordinated ester carbonyl in 2a-d with trimethylphosphite affords 3a-d as stable crystalline products.